2016
DOI: 10.1038/ejhg.2015.281
|View full text |Cite
|
Sign up to set email alerts
|

Genomic complexity of urothelial bladder cancer revealed in urinary cfDNA

Abstract: Urothelial bladder cancers (UBCs) have heterogeneous clinical characteristics that are mirrored in their diverse genomic profiles. Genomic profiling of UBCs has the potential to benefit routine clinical practice by providing prognostic utility above and beyond conventional clinicopathological factors, and allowing for prediction and surveillance of treatment responses. Urinary DNAs representative of the tumour genome provide a promising resource as a liquid biopsy for non-invasive genomic profiling of UBCs. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 29 publications
4
103
0
Order By: Relevance
“…These studies are important because they demonstrated the feasibility of NGS approaches on cfDNA in urine,85 even presenting a higher tumor genome burden in the cell-free fraction than in the cell sediment 84. All these results indicate further applications of ucfDNA in tumors.…”
Section: Urine Cfdnamentioning
confidence: 80%
“…These studies are important because they demonstrated the feasibility of NGS approaches on cfDNA in urine,85 even presenting a higher tumor genome burden in the cell-free fraction than in the cell sediment 84. All these results indicate further applications of ucfDNA in tumors.…”
Section: Urine Cfdnamentioning
confidence: 80%
“…However, even when excluding clinically metastatic patients likely to have a very low or absent tumor burden (e.g., those with pathologic lymph node disease), there remained some plasma cfDNA samples from patients with metastasis that yielded no ctDNA evidence. Our assay was also relatively uninformative in the localized setting, although the availability of tumor tissue collected at transurethral resection (or cystectomy) and urinebased biomarkers reduce the rationale for pursuing plasma ctDNA in this setting (27,41). Nevertheless, future studies seeking to capture somatic information from all patients with metastasis could augment targeted panel sequencing with ddPCR for patient-specific mutations identified through archival tissue analyses or for recurrent hotspot mutations (e.g., in PI3KCA or TERT), as has been applied successfully to patients with clinically localized bladder cancer (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, analyzing tyrosine kinase inhibitor‐resistance in NSCLC patients indicated by the EGFR p.T790M mutation is currently the only application for liquid biopsy in routine diagnostics. The general feasibility of this approach was demonstrated not only in clinical studies, but also in first studies related to routine diagnostics, and some reports showed that the resistance‐conferring mutation was often detectable in ctDNA prior to clinical progression . Although a low amount of ctDNA copies may be close to noise, data in osimertinib treated, EGFR p.T790M‐positive NSCLC patients indicated response even with less than 10 DNA copies per milliliter plasma .…”
Section: Liquid Biopsy For Mutation Testing In Different Diagnostic Smentioning
confidence: 99%